2022
DOI: 10.4178/epih.e2022109
|View full text |Cite
|
Sign up to set email alerts
|

Non-cancer health risks in firefighters: a systematic review

Abstract: Firefighters are occupationally exposed to hazardous factors which may increase their risk of disease.Non-cancer disease risk in firefighters has not been systematically examined. This systematic review aimed at identifying non-cancer disease risk in firefighters and determining whether a risk difference exists according to job characteristics.We searched the Cochrane Library, Embase, PubMed, and KoreaMed databases using relevant keywords from their inception to April 30, 2021. The Risk of Bias Assessment Tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…For this reason, firefighters work with the potential risk and possibility of contracting job-related diseases, such as cancer, acute and chronic lung diseases and water-borne diseases [31,42]. If firefighters do not wear PPE completely at the scene of a water accident, they may ingest water-borne viruses or bacteria contained in the water, and vomiting, diarrhea or pneumonia may occur depending on the individual [43,44]. Firefighters engaged in fire work increase the risk of developing cancer by being continuously and repeatedly exposed to carcinogenic substances.…”
Section: Guide To Personal Protective Equipment For Firefighter Healt...mentioning
confidence: 99%
“…For this reason, firefighters work with the potential risk and possibility of contracting job-related diseases, such as cancer, acute and chronic lung diseases and water-borne diseases [31,42]. If firefighters do not wear PPE completely at the scene of a water accident, they may ingest water-borne viruses or bacteria contained in the water, and vomiting, diarrhea or pneumonia may occur depending on the individual [43,44]. Firefighters engaged in fire work increase the risk of developing cancer by being continuously and repeatedly exposed to carcinogenic substances.…”
Section: Guide To Personal Protective Equipment For Firefighter Healt...mentioning
confidence: 99%
“…Furthermore, the urgency of re ghting tasks to meet the golden hour for re ghting, rescue, and emergency medical activities can lead to circadian rhythm disruption and stress [13]. A systematic review on non-cancerous health risks among re ghters [14] found that re ghters have a higher risk of mental disorders, hearing impairment, myocardial infarction, and ischemic stroke than the general population. The International Agency for Research on Cancer has classi ed re ghting as a Group 1 carcinogen owing to the elevated risk of cancer associated with occupational exposure among re ghters.…”
Section: Introductionmentioning
confidence: 99%